Perception and Acceptance of the Newly Introduced COVID-19 Precaution (THIRD) Vaccination Dose among Health Workers at an Indian Medical College - Shibaji Gupta; Arup Chakraborty; Sucharita Maji; Abhishek De; Arista Lahiri; Debasis Das (Indian Journal of Public Health)
Introduction: India has run a nationwide vaccination campaign against COVID-19, which has recently introduced a precaution (third) dose for health workers. This study assessed the perception and attitude of health workers toward the Indian vaccination campaign against COVID-19, with an emphasis on this major change. Materials and Methods: A printed questionnaire was distributed among health-care workers at the Medical College of West Bengal. The completed forms were analyzed. Results: Most of the participants were doctors (83.7%). Although all had received two doses of vaccine before, 44.4% were unwilling to be vaccinated with the third dose in the present scenario. The majority (63.8%) of the patients were concerned about side effects. The emergence of new COVID strains (65.6%) was viewed as a threat to the effectiveness of the vaccines. Participants with higher age, comorbidities, and those with the perception that the third dose was being introduced appropriately and would be effective against newer strains of the vaccine tended to be more willing to get vaccinated with the precaution dose compared to their counterparts. Conclusion: A dilemma regarding the acceptance of precaution doses was noted among health workers. This warrants the availability of more comprehensive information to increase acceptance of these vaccines.